1973
DOI: 10.1152/ajplegacy.1973.225.3.683
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic regulation of secretion and transductal fluxes of ions in the rat parotid

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…lt should be noted that the decline in the secretory response following attainment of maximum rates of secretion is far more rapid than could reasonably be expected on the basis of falling plasma concentrations; a similar phenomenon seen during continuous acetylcholine stimulation has been interpreted as due to some form of gland desensitization brought about by continuous stimulation (Case et al, 1979). in the parotid gland the maximum flow response was not more than 20% of what can be elicited with pilocarpinc, carhachol or acetyicholine (Mangos and Braun, 1966;Mangos et «/., 1973: Young andvan Lennep, 1979) but was of similar magnitude to that evoked by isoproterenol (Mangos et al, 1973). It is clear that, ofthe three major salivary glands ofthe rat.…”
Section: Flow Responsesmentioning
confidence: 89%
See 1 more Smart Citation
“…lt should be noted that the decline in the secretory response following attainment of maximum rates of secretion is far more rapid than could reasonably be expected on the basis of falling plasma concentrations; a similar phenomenon seen during continuous acetylcholine stimulation has been interpreted as due to some form of gland desensitization brought about by continuous stimulation (Case et al, 1979). in the parotid gland the maximum flow response was not more than 20% of what can be elicited with pilocarpinc, carhachol or acetyicholine (Mangos and Braun, 1966;Mangos et «/., 1973: Young andvan Lennep, 1979) but was of similar magnitude to that evoked by isoproterenol (Mangos et al, 1973). It is clear that, ofthe three major salivary glands ofthe rat.…”
Section: Flow Responsesmentioning
confidence: 89%
“…1975). One study on the effect of isoprenaline on the rat parotid has been published (Mangos, McSherry and Arvanitakis, 1973), and it is known that this drug does not cause secretion by the rat sublingual gland (Martin and Young. 1971a).…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of the animals for micropuncture and saliva collections were as previously described by these authors for ferrets and rats. 1,2,4 In order to study the net water fluxes of the lobular and main ducts of these salivary glands, we used the method of split-oil droplet stationary microperfusion technique originally developed by Shipp et al method has been used in this laboratory for the study of the chloride and water fluxes in the interlobular ducts of the rat pancreas.7…”
Section: Methodsmentioning
confidence: 99%
“…Salivary intra-and extralobular ducts are considered to be water impermeable (e.g., Mangos et al, 1973;Cook and Young, 1989) and A5 cells share immunological characteristics with such ducts in the rat submandibular gland. Further, two studies Li et al, 1994) ies and venules.…”
Section: Examination Of Salivary Cells For Aqpl Expressionmentioning
confidence: 99%
“…Although the experimental results are clear, they are also physiologically somewhat surprising. Salivary intra-and extralobular ducts are considered to be water impermeable (e.g., Mangos et al, 1973;Cook and Young, 1989) and A5 cells share immunological characteristics with such ducts in the rat submandibular gland. Further, two studies Li et al, 1994) have demonstrated that AQPl is not expressed by any epithelial cells (ductal and acinar) in this gland.…”
Section: Examination Of Salivary Cells For Aqpl Expressionmentioning
confidence: 99%